2004
DOI: 10.1002/ppap.200400025
|View full text |Cite
|
Sign up to set email alerts
|

Surface Analysis of Plasma‐Deposited Polymer Films, 3

Abstract: Summary: Pulsed‐plasma‐deposited ethylene films were studied by time‐of‐flight static secondary ion mass spectrometry (ToF‐SSIMS) before and after exposure to ambient air. The influence of the external plasma parameters on the secondary ion mass spectra of plasma‐deposited ethylene films was investigated. From these data, information on the chemical character of the plasma‐deposited ethylene films was derived. The investigation of the effect of external plasma parameters on the chemical character of the plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
38
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 21 publications
8
38
0
Order By: Relevance
“…Moreover, the peaks at 3030, 1605 and at 905 cm -1 could be attributed to the existence of vinyl groups in the deposited film [35,36]. Tibbit et al [37], Donohoe and Wydeven [38], Oran et al [39] and Swaraj et al [40] have pointed out that the plasma polymerization of ethylene yields a plasma-polyethylene polymer with different structural characteristics with respect to that obtained with conventional methods. The plasmapolyethylene polymer possesses chemical crosslinks, ramifications and unsaturated vinyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the peaks at 3030, 1605 and at 905 cm -1 could be attributed to the existence of vinyl groups in the deposited film [35,36]. Tibbit et al [37], Donohoe and Wydeven [38], Oran et al [39] and Swaraj et al [40] have pointed out that the plasma polymerization of ethylene yields a plasma-polyethylene polymer with different structural characteristics with respect to that obtained with conventional methods. The plasmapolyethylene polymer possesses chemical crosslinks, ramifications and unsaturated vinyl groups.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have indicated that cell-surface interactions are governed by the physico-chemical properties of the surfaces such as chemical functional groups, surface energy, roughness and surface charge [13,[19][20][21][22][23][24][25][26]. These interactions can be classified as either physical (adsorption), or chemical (covalent bonding) or a combination of both, e.g., electrostatic attraction of a bio-molecule onto an oppositely charged surface [27].…”
Section: Introductionmentioning
confidence: 98%
“…1 Many attempts, involving physical and chemical interactions, have been made to improve the surface chemical and mechanical properties of polymer. 2 Plasma polymerization technique is considered to be a unique method of preparation of thin polymeric films and the application of this technique to several fields has been studied by various researchers.…”
Section: Introductionmentioning
confidence: 99%